2014
DOI: 10.1074/jbc.m114.561902
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding Protein TDP-43 Selectively Disrupts MicroRNA-1/206 Incorporation into the RNA-induced Silencing Complex

Abstract: Background: Regulation of microRNA activity independent of processing and biogenesis has not been demonstrated.Results: The RNA-binding protein, TDP-43, interacts with mature miR-1/miR-206, limiting their RNA-induced silencing complex (RISC) association and activity.Conclusion: RNA-binding proteins can selectively control microRNA activity by disrupting RISC incorporation.Significance: This is the first known microRNA-protein interaction that controls microRNA activity independent of processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…TDP-43 plays a role in miRNA biogenesis, has been linked to the inhibitory effect of miRNAs on their targets by interacting with mature and pri-miRNAs, and is known to prevent the incorporation of selected miRNAs into the RISC (Buratti et al, 2010; Emde et al, 2015; Kawahara and Mieda-Sato, 2012; King et al, 2014; Li et al, 2013b; Zhang et al, 2013); therefore, we were interested in determining whether TDP-43 plays a role in the miRNA-induced regulation of one of our selected target genes, EIF2C4/AGO4. AinV15 mES cells conditionally expressing N-Flag-TDP-43 under control of a Dox-inducible promoter were transiently transfected with a luciferase reporter expressing the 3’ UTR of EIF2C4/AGO4 in the presence or absence of Dox.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TDP-43 plays a role in miRNA biogenesis, has been linked to the inhibitory effect of miRNAs on their targets by interacting with mature and pri-miRNAs, and is known to prevent the incorporation of selected miRNAs into the RISC (Buratti et al, 2010; Emde et al, 2015; Kawahara and Mieda-Sato, 2012; King et al, 2014; Li et al, 2013b; Zhang et al, 2013); therefore, we were interested in determining whether TDP-43 plays a role in the miRNA-induced regulation of one of our selected target genes, EIF2C4/AGO4. AinV15 mES cells conditionally expressing N-Flag-TDP-43 under control of a Dox-inducible promoter were transiently transfected with a luciferase reporter expressing the 3’ UTR of EIF2C4/AGO4 in the presence or absence of Dox.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, TDP-43 binds to miRNAs and components of the miRNA-processing pathway at different steps, exhibiting direct interactions with mature miRNAs, nuclear pri-miRNAs, the nuclear RNAse Drosha, and the cytoplasmic RNAse Dicer (Buratti et al, 2010; Emde et al, 2015; Kawahara and Mieda-Sato, 2012; King et al, 2014; Li et al, 2013b; Zhang et al, 2013). In addition, TDP-43 also affects how miR-206, a skeletal muscle-specific miRNA involved in neuromuscular junction re-innervation in ALS animal models and following nerve injury, incorporates into the RISC (King et al, 2014). Our data suggests that TDP-43, in part, may regulate the function of miRNAs decreased in sALS spinal cord as well as their downstream targets, perhaps by the sequestration of miRNA biogenesis components to stress granules upon stress (Emde et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining their combinatorial effects would be of great interest. In addition, microRNA effects can be regulated by a variety of binding proteins (Hammell et al, 2009; King et al, 2014) and it is possible that interactions with such regulators inhibits miR-222’s effects at baseline but this inhibition is released in response to a second stimulus, such as ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, the mapping of microRNA-target interactions during physiologic perturbations of primary tissues using methods such as high-throughput sequencing of RNA isolated by cross-linking immunoprecipitation or photoactivatable-ribonucleoside-enhanced cross-linking and immunoprecipitation may help shed light on these issues. Furthermore, recent studies have reported additional ways in which microRNAmRNA interactions can be altered, including changes in subcellular localization of microRNA-Ago complexes (32-34), expression of endogenous microRNA "sponges" (35), microRNA editing (36), interference by RNA-binding proteins (16,37), changes in RNA secondary structures (38), use of alternative polyadenylation sites in target mRNAs (39), or disruption of microRNA-Ago interactions (40). All these factors collectively may contribute to the distribution of individual microRNAs between HMW-RISC and LMW-RISC in vivo.…”
Section: Discussionmentioning
confidence: 99%